Experimental investigation of damage and failure in composite sandwich panels - Chan, Ambrose Kai Cheong. (2009)
The aim of the project is to study and understand the structural response due to contact between an impactor and a sandwich panel. This project involves the fabrication of sandwich panel specimen and experimental investigation of its behavior under quasi static loading. Sandwich panel specimens will be tested on both the test rig and on the flat bed. In order to evaluate the sandwich panel’s behavior under static load, sandwich panels that has been fabricated without adhesive between the laminates and honeycomb core interface will also be tested, both on the test rig and on the flat bed also. The orientation [45/-45/0/90/0]s has been selected for the above type of experimentation. Core sizes of 3mm, 6mm and 13mm, and core thickness 15mm, 20mm and 25mm are also selected for this project. The specimens are all fabricated into sizes of 100mm by 100mm.